Extracellular Vesicles in Transplantation - Sailliet, Nicolas; Ullah, Matti; Dupuy, Amandine; Silva, Amanda K. A.; Gazeau, Florence; Le Mai, Hoa; Brouard, Sophie (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) have been extensively studied in the last two decades. It is now well documented that they can actively participate in the activation or regulation of immune system functions through different mechanisms, the most studied of which include protein–protein interactions and miRNA transfers. The functional diversity of EV-secreting cells makes EVs potential targets for immunotherapies through immune cell-derived EV functions. They are also a potential source of biomarkers of graft rejection through donor cells or graft environment-derived EV content modification. This review focuses on preclinical studies that describe the role of EVs from different cell types in immune suppression and graft tolerance and on the search for biomarkers of rejection.